Mutiny under the Sun: The Connaught Rangers, India, 1920. (April 2020) - Draper, Mario
This article re-examines the causes of the Connaught Rangers mutiny and argues that institutional failings in the British Army were far more influential in the breakdown of discipline than the oft-supposed politicization of its participants. New and under-used source material demonstrates how the popular myth surrounding the actions of James Daly and his co-conspirators was nothing more than a self-serving exaggeration of events designed to fit an idealized Nationalist narrative of Irish resistance to British rule. More compelling is the argument that demobilization left the regiment with an imbalance in officer–man relations that tipped a combustible situation over the edge.